Design and Implementation of Food & Beverage Order Applications Using Multilevel Feedback Queue Method Based Android (case Study : Bonk Cafe Krian) - Muchammad Ilyas; R Dimas Adityo; Rani Purbaningtyas (Fakultas Teknik Universitas Bhayangkara, 2017)
With the development of information technology that exists today everyone can perform data processing easily, canproduce an information we need accurately and save time, as well as cost. Then we need a menu applicationapplication program using smartphone technology and web based to facilitate the ordering of food and drinks atBonk Cafe Krian. With the features that exist in this application, the user can make the ordering process usingAndroid and from the order will be stored into the database server so that the ordering process will appear on themonitor the kitchen along with the cashier. This Android-based service application has a significant time differenceso that this application can save time and speed up the service process.Multilevel Feedback Queue algorithm as a method that can increase the efesiesi time and speed up serviceprocess to the customer. With this algorithm can be built an application ordering android-based food and beveragethat is light and reliable.Functionally in Results in this test requires 4 customer data with different kinds of menus that have differentorder times, scheduling results in estimated waiting time and presentation time to customers with an average of 3.25minutes. So the food and beverage system is declared feasible test and feasible to be used functionally.